PERAN GENERASI MUDA DALAM MENGELOLA MEDIA SOSIAL SECARA PRODUKTIF DI SMA PGRI 2 DEPOK - Alhayu Rifhatul Fikriyah; Indah Nurfebriani; Rheva Deo Pratama (LAP4B, 2026)
The development of information and communication technology in the digital era has brought about significant changes in people's lives, particularly in communication patterns, information dissemination, and social interaction. The presence of social media makes it easy for people to obtain information, build communication, expand social networks, and develop creativity without being limited by space and time. However, uncontrolled use of social media can lead to various negative impacts such as digital addiction, the spread of fake news (hoaxes), cyberbullying, and decreased productivity. This Community Service (PKM) activity was conducted by students of the Faculty of Economics and Business, Pamulang University, at SMA PGRI 2 Depok on May 21, 2026, with the theme